Language and its philosophy in the views of Al-Farabi: a discussion in the light of the Quran - Shuaibu Umar Gokaru,; Mustaffa Abdullah,; Faisal @ Ahmad Faisal Abdul Hamid,; Youcef Bensala, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Muslims and non-Muslims of the classical and contemporary world believe that Al Farabi (870-950) was the most important personality in the science of language, philosophy, speech, and culture. This reason led various scholars to argue on the exact intent of Al-Farabi on language. To what extent the intent of Al-Farabi in his mind about language and its philosophy be analysed in the light of the Quran? This is directly overlooked by various researchers, and it is the main purpose of this article. A descriptive approach is used in this article by gathering data about the language and its philosophy of Al-Farabi. The researchers investigate, identify, explain, and answer the question based on the data collected. The qualitative method is used for data analysis to understand the intent of language and its philosophy of Al-Farabi in the light of the Quran. The findings show that analysing the views of Al-Farabi in the light of the Quran is of great importance as his knowledge of Islamic teachings influenced most of his ideas, in which he believed that language must be clear, eloquent, comprehended, and understood by those who are speaking with it, and it is what the Quran exactly declared. In other words, the finding further indicates that language and its philosophy in the views of Al-Farabi should be, its wordings and texts must be matched and presents the same information without contradiction.